UPAYA PENURUNAN TINGKAT KANIBALISME RAJUNGAN (Portunus pelagicus) DENGAN PEMBERIAN SUPLEMEN TRIPTOFAN - Suharyanto Suharyanto; Yani Aryati; Suwardi Tahe (Universitas Gadjah Mada, 2008)
The aim of this experiment was to find out the suitable dosage of tryptophan mixed in diet of trash fish were fed and to decrease canibalism levels of swimming crabs (Portunus pelagicus) reared in fiber glass tanks. The research was conducted in research station of Research Institute for Brackishwater Aquaculture Maranak, Maros South Sulawesi on 8th May to 8th June 2006. Twelve fiber glass tanks were used of this research and the dimention of 1 x 1 x 0.5 m. Crablet of 17th from hatchery were used to this research and the dimention of 7.2 + 0.2 mm width and 0.05 + 0.02 g body weight. Hundred crablets were spreaded on the each tanks. The treatments were applied of dosage of tryptophan were mixed in the trash fish (Sardinella sp) as much as (A): 0% of biomass total, (B): 0.5%, (C): 1.0% and (D): 1.5% of biomass total with three replicates respectively. Variables monitored growth of charapace width and body weigth, canibalism levels, survival rate of swimming crab and water quality. Experimental design used complate randomized design. During of rearing were fed trash fish (Sardinella sp) with frequency of three times a days of dosage 15% of total body weight. The result showed that the crablet fed the diet with additional 1.5% tryptophan had significantly lower (P<0.05) cannibalisms compared to the crablet feed the control diet. The crablet fed the diet with additional 1.5% tryptophan had significantly higher (P<0.05) survival rate compared to the crablet fed the control diet. However, there were not significantly different specific growth rate among the treaments. Based on this result that additional 1.5% tryptophan could be decrease cannibalisms of swimming crabs crablet during experiment.